Intelligent Compaction Technique as a Tool of Objective and Effective Application af Geosynthetics - Izvolt, Libor; Kardos, Jan (Communications - Scientific Letters of the University of Zilina, 2010)
The paper focuses on evaluation of the current state of designing and realization of railway substructure layers on modernized Slovak railway tracks with the emphasis on an effective use of geosynthetic products. The presented method of intelligent compaction may significantly increase efficiency of design and realization of construction layers with the objective use of geosynthetics and other adjustments at various geological conditions of subgrade.
Keywords: no keywords